The advertisement call of Elachistocleis helianneae Caramaschi, 2010 (Anura: Microhylidae) - Da Fonseca, Emanuel Masiero; Lanna, Flávia Mól; Sant’ Anna, Anathielle Caroline; Pereira, Elvis Almeida; Santos, Felipe Ferreira Dos; de Oliveira Neves, Matheus; Mângia, Sarah (Zootaxa, 2012)
The genus Elachistocleis Parker, 1927 currently comprises 13 species, not considering E. ovalis (Schneider, 1799) (see Caramaschi 2010). This genus occurs in Central America and most of South America, from Panama to Argentina, including Venezuela, Bolivia, Colombia, Guyana, Surinam, French Guiana, Paraguay, Uruguay, and Brazil (Frost 2011; Nunes-de-Almeida & Toledo 2012). Elachistocleis helianneae Caramaschi, 2010 was described from Humaitá, state of Amazonas, and occurs in northern Brazil, in the states of Amazonas, Pará and Rondônia, and in Bolivia, in the departments of Beni and Santa Cruz (Caramaschi 2010).